Highly efficient synthesis of benzyl benzoate directly from self-coupling of benzyl alcohol in water - Zewei Dou; Zihuai Xu; Tao Zhang; Shengnan Li; Chengyu Xu; Tianbo Fan; Hongfan Guo (Resources Chemicals and Materials, 2023)
Benzyl benzoate (BB), an important ester, still demands for green synthesis routes. In this work, by size regulation and proper functionalization of carbon nanotubes (CNTs) as the support of gold catalyst, this ester can be synthesized very efficiently directly from benzyl alcohol via oxidative coupling. More attractively, the reaction is performed using water as green solvent and molecular oxygen as green oxidant. Simultaneously, very high selectivity to BB can be obtained near full conversion within very short reaction time (just 0.5 h), while the low-value benzoic acid byproduct is negligible. This is very different from many reported gold catalysts that yield much benzoic acid and/or benzaldehyde in water. The results show that, besides the size of CNTs (length and diameter), the functionalization of CNTs is also critical for improving both conversion and the selectivity to BB. In addition, the reaction mechanism for forming BB ester is put forward as well.